Development of a novel fly ash-polyacrylamide nanocomposite gel system for improved recovery of oil from heterogeneous reservoir - Singh, R.; Mahto, V.; Vuthaluru, Hari (Elsevier, 2018)
© 2018 Elsevier B.V. Among all the available methods to reduce water production and to improve oil recovery from heterogeneous reservoirs, injecting a gelling system composed of a polymer and a crosslinker has been widely used. A novel nanocomposite hydrogels used to reduce excessive water production from heterogeneous reservoir was systematically analyzed. The nanocomposite used in this work was synthesized using nano fly ash and acrylamide by free radical polymerization and hydrogel was prepared by crosslinking a fly ash-polyacrylamide nanocomposite with chromium acetate. The bottle and breakthrough vacuum tests were conducted to gain insight into the gelation time and gel strength of nanocomposite hydrogel respectively. The effect of various parameters such as polymer concentration, crosslinker concentration, nano fly ash concentration and temperature on gelation time and gel strength was systematically evaluated. From the results, it was observed that the nanocomposite gel system has enough gel strength (0.045 MP) and acceptable gelation time (9–10 h). In addition, sand pack flooding experiments revealed that the nanocomposite polymer gel has good plugging capacity at reservoir conditions (95.14% at 90 °C), indicating its potential to recover additional oil from matured oil fields having natural or induced fractures and permeability variations in the reservoirs.